2007
DOI: 10.1111/j.1365-2621.2006.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size and drying temperature on drying rate and oil extracted yields of Buccholzia coriacea (MVAN) and Butyrospermum parkii ENGL

Abstract: The effect of particle size and drying temperature on drying rate and oil extracted yields of Buccholzia coriacea (MVAN) and Butyrospermum parkii (ENGL) was investigated. Air drying studies carried out on B. coriacea and B. parkii, tropical food sources subject to high post-harvest losses, have resulted in the establishment of a significant difference between oil yields extracted from samples of various particle size pretreatments (paste, 4 mm, 8 mm and whole kernels) dried at 45 and 60°C with the highest oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 5 publications
2
23
0
Order By: Relevance
“…The chemical composition of shea kernels used in this work is summarized in Table 2. Fat content (31.32 ± 1.04%) was almost similar to the values reported by other researchers (Womeni et al 2006;Kapseu et al 2007) but lower than the value (47.47%) reported by Bup Nde et al (2012). Data analysis of water content of dry shea nuts generated a regressive equation expressing the water content of shea nuts influenced by drying temperature and time of shea nuts (Eq.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The chemical composition of shea kernels used in this work is summarized in Table 2. Fat content (31.32 ± 1.04%) was almost similar to the values reported by other researchers (Womeni et al 2006;Kapseu et al 2007) but lower than the value (47.47%) reported by Bup Nde et al (2012). Data analysis of water content of dry shea nuts generated a regressive equation expressing the water content of shea nuts influenced by drying temperature and time of shea nuts (Eq.…”
Section: Resultssupporting
confidence: 70%
“…A contribution has been done by Womeni et al (2006), Kapseu et al (2007), Aculey et al (2012), andBup Nde et al (2012). However, x 1 -cooking temperature; x 2 -nuts/water ratio; x 3 -cooking time; x 4 -drying temperature; x 5 -drying time; +α -highest coded level of the variables; -α -lowest coded level of the variables neither the variation of cooking parameters combined with drying parameters nor the cooking mass ratio (nuts/water), which is also a possible influencing parameter, have been investigated yet.…”
mentioning
confidence: 99%
“…Previous studies on the processing of shea nuts into butter (Womeni, 2004;Kapseu et al, 2007;Bup et al, 2011) have not assessed the relationship between roasting time and temperature during shea processing on the yield and quality, including the volatile compounds of the butter. The main objective of this study was therefore to assess the impact of roasting conditions of shea kernels on fat yield, and on the FFA percentage, peroxide value and volatile compounds of the butter to optimise production practices in rural, low-input settings.…”
Section: Introductionmentioning
confidence: 99%
“…Among the traditional unit operations in shea kernel processing, roasting is reported to be critical for butter quality and yield (Womeni, 2004;Kapseu et al, 2007). Crushed shea kernels are commonly dry roasted for 30 -60 min in a pot with direct heating by firewood (Honfo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fresh sheanut kernels are big in size with average major, intermediate and minor diameters of 4.2 cm, 2.8 cm and 2.4 cm respectively (Nde Bup et al, 2011). Kapseu et al (2007) demonstrated that due to this large size, drying of whole kernels at 45°C took 12 days and equally led to the development of surface coat which hindered further drying suggesting that the kernels could be diced into smaller size before drying to shorten drying times. The popularly used sun drying method, though relatively cheap, is long (5-20 days) and exposes the dried kernels to rain and attack by micro-organisms and insects.…”
Section: Introductionmentioning
confidence: 99%